Effects of Yoga Poses on Spinal Range of Motion, Posterior Superior Iliac Spine Levels and Muscle Activity According to Pelvic Displacement in Middle-aged Women - Ah-Ram Kim; Sun-Ah Lee; Ho-Seong Lee (Asian Society of Kinesiology, 2018)
PURPOSE The purpose of this study was to investigate the effects of yoga poses on spinal range of motion, posterior superior iliac spine levels and muscle activity according to pelvic displacement in middle-aged women. METHODS Twenty middle-aged women were selected to normal pelvic displacement group (CON, n=6), anterior pelvic tilt group (APG, n=6) and posterior pelvic tilt group (PPG, n=8). Spinal range of motion, posterior superior iliac spine levels and muscle activity were measured during Yoga poses (Janusirsa asana, parivrrta upavistha konasana, parsva upavistha konasana, virabaddra asana III). RESULTS The following were the main results. Right trunk flexion and pelvic tilt during right janushirasana asana were significantly decreased at APG and PPG compared to CON (p<.05, respectively). Also, pelvic tilt during right parivrrta upavistha konasana was significantly decreased at APG and PPG compared to CON (p<.05, respectively). Furthermore, muscle activity in the erector spine, glutes medius, biceps femoris, and gastrocnemius during yoga poses were significantly increased at APG compared to CON (p<.05, respectively), and muscle activity in the glutes medius during yoga poses was significantly increased at PPG compared to CON (p<.05). CONCLUSIONS These results confirms that yoga poses in middle-aged women with pelvic displacement make a negative effect on spinal joint motion range, posterior superior iliac spine levels and muscle activity.